Characteristics of Wave Breaking and Blocking by Spatially Varying Opposing Currents. Issue 5 (24th May 2018) - Chen, Haifei; Zou, Qingping
Abstract: A Reynolds‐Averaged Navier‐Stokes (RANS) flow solver with a Volume of Fluid (VOF) surface capturing scheme is used to investigate wave breaking and blocking due to strong opposing currents. The Shear Stress Transport (SST) k − ω model is modified in order to capture the turbulence properly. The unique capability of the RANS‐VOF model allows us to reveal the distinct features of current‐induced wave breaking and blocking. The limiting wave steepness at breaking onset is reduced considerably by the opposing current from the Stokes' limit for stationary waves. Although the wave height grows faster before breaking under a more rapidly varying current, the maximum height at the breaking onset remains almost the same. The locations of incipient breaking are slightly shifted downstream/upwave by the increased current gradient. It was found that the wave radiation stress alters the mean water level by competing with the pressure gradient arising from the current‐induced surface tilting. The wave set‐down and set‐up is more pronounced for more intensive breakers occurring under a larger incident wave and current gradient. Our model results indicate an undertow‐like change to the current profile due to wave breaking. The turbulence and vorticity generated by the current‐induced breaking wave persist and are advected downstream and interact with those generated by the following wave and current. Key Points: Current‐induced breaker has a limiting wave steepness of ak  = 0.3, much smaller than that for a Stokes wave at deep water Wave set‐down and set‐up exist by competing with the pressure gradient caused by the current‐induced surface tilting Turbulence and vorticity generated by breaking wave are advected downstream by current, and interact with those generated by the following wave and current